PERAN ISTRI SEBAGAI WANITA KARIR DALAM MEWUJUDKAN KEHARMONISAN KEHIDUPAN RUMAH TANGGA DI DESA WAJAK KECAMATAN WAJAK KABUPATEN MALANG - M. Anwar Fuadi; Khoirul Asfiyak; Humaidi Kaha (Jurnal Hikmatina, 2022)
The role of a wife is to serve her husband and raise children and be the main madrasa for a child. As for being a wife, it is not forbidden to have a career in the field. With the existence of gender justice, this causes justice for a woman to be able to have a career. However, Islam still respects and upholds the status of women. In Islamic teachings it does not prohibit women from having a career or working outside the home on condition that they do not neglect their obligations as housewives and do not violate the rights of their husbands or exceed the limits of their husband's leadership. The main goal in carrying out the role of being a wife and being a career woman in realizing harmony in the household is also based on mutual understanding, openness, trust in each other and being able to divide time appropriately. With the rights and obligations of husband and wife so that it appears the relationship between the two, namely between husband and wife, they must complement each other in various problems in the household